2004
DOI: 10.1523/jneurosci.3860-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Dual Control of Neurogenesis byPC3through Cell Cycle Inhibition and Induction ofMath1

Abstract: Growing evidence indicates that cell cycle arrest and neurogenesis are highly coordinated and interactive processes, governed by cell cycle genes and neural transcription factors. The gene PC3 (Tis21/BTG2) is expressed in the neuroblast throughout the neural tube and inhibits cell cycle progression at the G 1 checkpoint by repressing cyclin D1 transcription. We generated inducible mouse models in which the expression of PC3 was upregulated in neuronal precursors of the neural tube and of the cerebellum. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
101
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 61 publications
9
101
0
Order By: Relevance
“…Experiments in vitro and in vivo using different animal species have shown that Btg2 is expressed in differentiating neural precursors that switch from proliferative to neurongenerating division (Iacopetti et al, 1994(Iacopetti et al, , 1999, and that Btg2 overexpression results in negative regulation of the cell cycle and induction of neuronal differentiation (Malatesta et al, 2000;Corrente et al, 2002;elGhissassi et al, 2002;Canzoniere et al, 2004). Our results about Btg2 expression in the neural tube are consistent with those reported in mice.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Experiments in vitro and in vivo using different animal species have shown that Btg2 is expressed in differentiating neural precursors that switch from proliferative to neurongenerating division (Iacopetti et al, 1994(Iacopetti et al, , 1999, and that Btg2 overexpression results in negative regulation of the cell cycle and induction of neuronal differentiation (Malatesta et al, 2000;Corrente et al, 2002;elGhissassi et al, 2002;Canzoniere et al, 2004). Our results about Btg2 expression in the neural tube are consistent with those reported in mice.…”
Section: Discussionsupporting
confidence: 89%
“…Our results about Btg2 expression in the neural tube are consistent with those reported in mice. Interestingly, in vivo overexpression of Btg2 in mouse neuroepithelial cells affected cerebellar development by a mechanism that involves a double action of Btg2: (1) down-regulation of cyclin D1 promoting cell cycle exit, and (2) stimulation of Math1 promoter activity, stimulating differentiation of cerebellar progenitors located in the hindbrain rhombic lip (Canzoniere et al, 2004). Our results in the chick show that Btg2 is also highly expressed in the rhombic lip area, suggesting again a conserved function.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations